Ubiquitylation : its role and medical significance - Deák, Péter; Boros, Imre M. (Acta Biologica Szegediensis, 2015)
Ubiquitylation is an intracellular chemical reaction in which the small polypeptide, ubiquitin, is covalently attached to proteins to serve as a versatile signal with proteolytic and non-proteolytic functions. Although the importance of ubiquitylation was first recognized in the process of proteasome-mediated protein degradation, its regulatory potential has since been extended considerably. It is now known that through an elaborate and diverse set of ubiquitylating and deubiquitylating enzymes, the ubiquitin-proteasome system affects practically all intracellular processes. Not surprisingly, alterations in the ubiquitylating system have been linked to the development of various human diseases, including neurodegenerative disorders and cancer. Here, we highlight the most important components and processes of the UPS, and then demonstrate in a few examples connections between aberrations in ubiquitylation and the pathogenesis of certain diseases.